Transforming Education Through the Use of Blockchain Technology: Innovation in Educational Data Management - Felix Sutisna; Riya Widayanti; Fitra Putri Oganda; Shofiyul Millah; Sabda Maulana (Universitas Raharja, 2024)
This research focuses on exploring the application of blockchain technology in the management of educational data, aiming to identify the potential benefits and challenges of this technology in enhancing data security, transparency, and efficiency within educational institutions. The study also seeks to develop a conceptual framework that addresses the unique requirements and implications of blockchain integration in the academic sector. In an era where big data has become pervasive in business strategy, this research aims to understand the challenges and advantages of big data in the digital content sector related to environmental issues. The idea of “society 5.0” promotes harmony between technology and sustainable quality of life. Industry as an innovator plays an important role in offering solutions to social problems, and the digital content sector is considered to have great potential in achieving this goal. This research explores the concept of the digital content sector from a Society 5.0 perspective and discusses issues related to economics and sustainability. The importance of collaboration in creating a sustainable digital content sector is emphasized in the form of the concept of co-creation. Collaboration involves stakeholders from various levels of society, including industry, government, academia, and society, to accelerate innovation and share knowledge. In addition, the role of artists' skills in the creative sector is recognized as an important aspect that cannot be completely replaced by technology. This research also discusses the impact of the nation's innovation policies in supporting the growth and sustainability of the digital content sector. Policies that promote technological innovation, protect intellectual property rights, and provide incentives for companies that contribute to social and environmental sustainability, were identified as important factors in the development of the sector. Thus, this research explores the role of the digital economy, big data, and the concept of